Application of deterministic conceptual model for water balance studies (MAUSAM, 1980)
An attempt has been made to study the water balance of Dandavathy a tributory of Tungabadhara river basin in Karnataka by the application of Sacramento model which is a deterministic conceptual model.In this technique precipitation and the evaporation data have been used to allocate the moisture in various layers of the soil and the resultant runoff compared with the actual runoff for the purpose of the calibration of the model. The model is then used to study the water balance by the well known hydrologic equation and results are found to be very encouraging.